Strategy for Implementing Inclusive Education at Sekolah Indonesia Kuala Lumpur - Rupinis, Rupinis; Hariyati, Nunuk; Suryanti, Suryanti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to provide a comprehensive overview of the practice of inclusive education at Sekolah Indonesia Kuala Lumpur (SIKL). This research employs a qualitative method with a case study approach. Information sources were gathered from teachers, parents, and the school principal through semi-structured interviews. Observations were conducted using a non-participatory method, where the researcher acted as an observer of the implementation of inclusive education at Sekolah Indonesia Kuala Lumpur, encompassing the diversity of student practices. Documentation was collected from data on student diversity, supporting facilities for inclusive learning activities, and records of inclusive education evaluation results. Data analysis techniques employed triangulation, involving data collection, data reduction, verification, and drawing conclusions. The results of this study indicate that inclusive education at Sekolah Indonesia Kuala Lumpur is implemented through various strategies that support student diversity, including differentiated learning, multicultural classrooms, and innovative learning technologies. The positive impacts of inclusive education include students’ social development and increased student participation. This study recommends strengthening collaboration with external parties, enhancing teacher training, and developing policies that support the sustainability of inclusive education at Sekolah Indonesia Kuala Lumpur.